Monitoring CSA outcomes: Understanding adoption, synergies and tradeoffs at farmand household level - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Acosta, Ivonne; Chirinda, Ngonidzashe; García, María Alejandra; Twyman, Jennifer; Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
As part of the Learning Platform 2 on participatory evaluation of CSA practices and portfolios in Climate-Smart Villages, CCAFS Flagship 2 developed a multilevel monitoring plan. Designed to support global evidence building of viable climate smart agricultural practices and technologies, this plan is supported by an Integrated CSA framework associated to a robust, cost-effective and user friendly ICT-based instrument that can be rapidly, reliably and systematically deployed globally to track CSA adoption and outcomes in the field.